Documentação notarial e tabeliães públicos no porto na centúria de trezentos - Lopes, Joaquim (2013)
This article is the result of a Research Fellowship from FCT, which proposed the survey and transcription of some notarial documents compiled in the «Livros dos Originais» of the Porto Cathedral Chapter' reserve, from the Porto District Archive, dating from the second quarter to the end of the 1300’s. The importance of these documents for a better understanding of the Portuguese medieval notarial activity shifted the initial focus of this project to include, not only on a palaeographic study of the corpus, but also its diplomatic analysis.